Chemical effect on the mechanical properties of bamboo fiber for textile: a review - Mokeramin, Muslihah; Roslan, Mohd Nazrul; Abdul Rashid, Azrin Hani; Nasir, Siti Hana; Abdul Halip, Juliana (WARSE, 2020)
The needs on sustainable fiber of bamboo for textile and non-textile materials are never being doubt. The mechanical properties of bamboo fibers are unique among their species. Thus, this fiber requires a unique process to be implemented in order to meet their application. Often, previous studies had adopted various fiber extraction and treatment yet these processing were affected their physical and mechanical properties. Chemical treatments are often being applied onto natural fibers such as bamboo in order to improve crucial properties subjected to textile processing capability. Specifically, the treatment partially removes the cellulosic and non-cellulosic contents of the bamboo fiber bundle such as hemicellulose, lignin and pectin. An appropriate concentration of alkaline usage in treating bamboo fiber could obtain the optimum mechanical and physical performance along with the changes of its surface morphological. This paper provides a brief review on the published reports concerning on anatomical, chemical composition and physical of bamboo. The effect of alkaline treatment on bamboo fibers have been discussed and reviewed in terms of their mechanical behavior and physical properties.